Jouer les femmes : les concerts de musique contemporaine au Québec - Couture, Ariane (Recherches féministes, 2019)

Parcours dans la programmation des concerts du Nouvel Ensemble Moderne - Couture, Ariane (Circuit : musiques contemporaines, 2013)
During its 25 years of activities, the nem has played 635 works by 374 composers at local concerts, public workshops or world tours. Collectively, these works cover most of the aesthetic tendencies of the music of the 20th century. However, it is possible to define the repertoire of the ensemble along two main axes: on one hand, works that have become “classics” of contemporary music, and, on the other hand, new works engaged in musical innovation. Thus, the policy for disseminating works through concerts established by Lorraine Vaillancourt introduces a new culture within the world of musical creation, based on the development of a repertoire of works from the 20th and 21st centuries.
Publisher: Les Presses de l’Université de Montréal
Keywords: Nouvel Ensemble Moderne; concert; musical programming; programmation musicale; repertoire; répertoire